Peningkatan Kemampuan Menulis Teks Berita dengan Menggunakan Model Pembelajaran Project Based Learning pada Siswa Kelas VII SMP Negeri 3 Talang Muandau - Pardede, Maniar (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
Implementing the Project Based Learning (PBL) model has shown significant improvement in the ability to write news texts for seventh-grade students at SMP Negeri 3 Talang Muandau. This class action research utilized observation and instrument-based tests, including audiovisual presentations of national news videos and written post-test sheets, to collect data. Analysis involved individual and group scores, average student scores, and criteria-based assessment of student comprehension levels. Results revealed that in the first cycle, only 42% of students met the minimum completion criteria, with an average score of 55, while in the second cycle, all students met the criteria, achieving a 100% average score. Consequently, it can be inferred that the implementation of the PjBL model has significantly enhanced learning outcomes in news text writing for seventh-grade students at SMP Negeri 3 Talang Muandau.